ISLAMIC CSR RESEARCH AND TRENDS: A BIBLIOMETRIC ANALYSIS - Adi Susilo Jahja (Proceeding International Seminar of Islamic Studies, 2023)
Corporations need legitimacy from stakeholders; therefore, they should consider  the corporation's operations impact on society's welfare. CSR initiatives are essential to promote legitimacy. In this article, the Islamic CSR literature is bibliometric analysis is conducted using data from the Scopus database, revealing the intellectual structure of the CSR field of study. We believe that this is the first work that discuss Islamic CSR using bibliometric analysis. In the research method, Islamic CSR is used as a keyword in the titles of articles taken from the Scopus database. There were 163 documents analyzed using Microsoft Excel, VOSviewer, and Harzing’s Publish or Perish. We found the increasing number of publications about Islamic CSR, the common themes, and the most influential source regarding this topic.